Linking gut microbiota to aging process: a new target for anti-aging - Maoyang Lu; Zhao Wang (Food Science and Human Wellness)
The human gut microbiota is a huge ecosystem that provides lots of functions for host development, immune system, and metabolism. Gut microbiota is linked to lots of diseases, including human metabolic diseases such as obesity, type 2 diabetes (T2D), irritable bowel syndrome, and cardiovascular disease (CVD). Few studies, however, have noted the relationship between aging and microbiota, the connection between aging and microbiota remain largely to be researched. In this review, recent research findings are summarized on the role of gut microbiota in aging processes with emphasis on therapeutic potential of microbiome-targeted interventions in anti-aging medicine. Keywords: Gut microbiota, Aging, Fecal transplantation, Aging-related diseases